Analisis Perkembangan Dana Pensiun Syariah di Indonesia: Analisis Perkembangan Dana Pensiun Syariah di Indonesia - erpiana siregar (JIBF MADINA : Journal Islamic Banking and Finance Madina, 2023)
To ensure prosperity in a person's old age, every individual should prepare from an early age. To prepare for prosperity in old age, there is a financial industry that provides these services, namely pension funds. In Indonesia, pension funds are managed by the government and the private sector, such as BPJS Employment, which is a mandatory fixed contribution program for private and state-owned employees, Taspen, which is pension savings for civil servants and private pension programs, and ASABRI, which is the armed forces pension fund and pension funds for other financial institutions. Pension funds are managed using two principles, namely based on conventional principles which apply the interest system and sharia principles which apply sharia principles. Sharia pension funds were established in 2017, namely DPLK Muamalat in 2017, followed by DPLK Mandiri this year. In 2018 BNI also sold sharia investment packages. This year the OJK also approved the Jakarta Hospital Sharia Pension Fund. In 2019 OJK approved the Muhammadiyah Sharia Pension Fund. In 2020 OJK approved the Surakarta Muhamamadiyah Pension Fund. For clarity in sharia pension fund activities, it is centered on UPP No. 11 of 1992 concerning Pension Funds, then in 2013 DSN MUI fatwa No. 88 was issued concerning Management of Sharia Pension Funds, then in 2016 POJK No. 33 /POJK.05/2016 concerning Sharia Business Units.